The tourism clusters role in regional development : presenting a competitiveness conceptual model - Estevão, Cristina (2012)
Tourism is characterized for being a sector that has stood apart, as one of the business activities of the greatest expansion potential worldwide, and as an economical growth engine, which national impact is significant. But, if on a national level the importance of tourism is significant, on a more regional level this sector presents itself as an essential tool in regional development, as a mean to avoid regional desertification and stagnation of regions, by thrusting the natural and historical-cultural potential of the more undeveloped regions. On a world evermore global and competitive, it is of the most importance that companies develop strategic management, so that they may keep up to date with their environmental complexity, with the market trends and competitiveness, to obtain competitive advantage. Since it is unanimous that clusters increase the competiveness of a regional industry, and, since tourism is a powerful regional development tool, it is relevant and crucial to discuss the role of clusters in tourism. Clusters have become one of the most popular concepts of local and regional development, of research and exercise, because one of the goals of a tourism cluster is to lead companies that in a general manner work alone, to cooperate in the construct of a successful tourism product, to a given region. The aim of this paper is to present a competitiveness conceptual model, for a tourism cluster, for regional development. The main model characteristic is to emphasize the interaction between the determinants, to achieve competitiveness. Each determinant also enclosures a set of agents that promote pressure over the other determinant elements, so that the interaction degree defines the regional competitive advantage. In this model, competitiveness is the determining factor to a cluster’s success.